Effect of Coordinate Birch at Avtomobile Roads on the Average Time of Vegetation and Max-imum Width of Accounting Leaves - Matveevich Mazurkin, Peter; A.I, Kudryashova (European Journal of Applied Sciences, 2019)
For environmental assessment of the quality of the surrounding growing birch area in the summer of 2018, the width of 10 leaves of 10 birch trees hanging in the city of Yoshkar-Ola was measured. The distances from the edge of the road to the center of the birches were measured, as well as the height of the crown zone at each birch from the prevailing winds. The geographical coordinates of the trunk axis were measured by the cell phone, which were given to the conditional Northern latitude and Eastern longitude. From these influencing factors regularities of change of time of a Vegetation since may 1 and average maximum width of accounting leaves were received. The factor analysis of six influencing variables and two dependent indicators is carried out. Formulas and graphs are given. It is found that the influence of the distance from the road on the maximum width of the leaves has a correlation coefficient 0.7574, and the influence of the reduced East longitude on the same biometric parameter 0.7514. The average maximum width of the birch leaves can be a great indicator of pollution of the roadside area. To identify wave patterns, it is necessary to take more than 20 birches in different places.